Innovation strategies in Australian local government - Martin, John (2001)
A culture of innovation is seen as essential if local government organizations are to effectively manage and survive in ever-changing environments. This paper provides an overview of innovation processes and outlines how they are applied in four local government organizations. State and Federal Governments heavily regulate this sphere of Australian government. A culture of innovation provides an opportunity for local government to respond to pressing local needs within legislative and financial constraints. The paper concludes that for an innovative culture to develop in local government organizations, a number of interrelated factors must combine in a synergistic way for genuine organizational change to occur. Such an innovative culture develops when creative individuals respond to external pressure for change implementing new ways of working gleaned from an extensive network, both within and between organizations. This innovation reflects their personal desire for continuous learning, builds employee capacity across flexible organizations while working with long-term, best interests of the community they serve in mind.
Keywords: Innovation management; Local government personnel; Associations, institutions, etc